Persentase penambahan bagian telur ayam pada proses pengolahan amplang ikan lele dumbo (Clarias gariepinus) - Mukhammad Fauzi; Yuli Witono; Alfisyahrica Alfisyahrica; Astriani Astriani (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Amplang is a traditional food/cracker of East Kalimantan that is made by mixing mackerel, tapioca flour, eggs, and some seasonings. Innovation is needed to improve the local product of african catfish (Clarias gariepinus). The portion of egg has a different functions in the dough of amplang. This study aimed to determine the effect of the portion and percentage of eggs on the chemical, physical, and organoleptic characteristics of amplang made from catfish (Clarias gariepinus). The study used randomized group design (RGD) in factorial with two factors. The first factor (A) was the eggs that were added consisted of egg white, yolk, and mixed egg white and yolk (1:1). The second factor (B) was the percentage of eggs that were added to the weight of african catfish (20%, 30%, 40%). The result showed that the best characteristics of amplang were amplang A1B3 (40% of white egg): water content was 2.59% (bb); fat content was 20.39% (bb); protein content was 9.11% (bk); brightness value was 64.95; texture value was 526 gf/mm 2; blooming capacity was 440%; hygroscopicity was 1.22%; oil absorption 18.85%; color sensory value was 4.6 (like to very like); taste sensory value was 3.88 (rather like to like); crispness sensory value was 4.24 (like to very like); the overall sensory value was 4.32 (the favorable to the most favorable).